Desain Chassis Mobil Urban TITEN EV-2 Akibat Beban Dinamis - Muhammad Alwi Kurniawan Guhardiputra (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2023)
Chassis is a fundamental part of the vehicle that serves to support the overall load that works on thecar. Chassis also serves to keep the car's condition remains rigid and does not experience excessivedeformation and is safe when used. The selection of a strong but still lightweight material was carriedout, using 6061 aluminum material. In this study, an analysis of the TITEN EV-2 urban car chassisdesign will be carried out under dynamic loading when braking with variations in the Chassis profileshape, namely the profile in the form of square and rectangular hollow and the distance braking is15m. The purpose of this study is to determine the effect and optimal conditions of the designparameters in the form of a profile on the chassis of an electric car. By using the finite element method,the strength analysis of the chassis structure design can be determined by looking at the maximumstress and total deformation acting on the chassis. From the simulation results, the rectangular hollowchassis profile has a mass of 7.6 kg which is lighter than the square hollow chassis which has a massof 9.4 kg. Rectangular hollow chassis has a maximum stress that is superior to square hollow chassisat loading distances 15 m.